The interplay between psychopathological symptoms: transdiagnostic cross-lagged panel network model. Issue 4 (27th July 2022) - Chavez-Baldini, UnYoung; Verweij, Karin; de Beurs, Derek; Bockting, Claudi; Lok, Anja; Sutterland, Arjen L.; van Rooijen, Geeske; van Wingen, Guido; Denys, Damiaan; Vulink, Nienke; Nieman, Dorien
Abstract : Background: Recent paradigm shifts suggest that psychopathology manifests through dynamic interactions between individual symptoms. Aims: To investigate the longitudinal relationships between symptoms in a transdiagnostic sample of patients with psychiatric disorders. Method: A two-wave, cross-lagged panel network model of 15 nodes representing symptoms of depression, (social) anxiety and attenuated psychotic symptoms was estimated, using baseline and 1-year follow-up data of 222 individuals with psychiatric disorders. Centrality indices were calculated to determine important predictors and outcomes. Results: Our results demonstrated that the strongest relationships in the network were between (a) more suicidal ideation predicting more negative self-view, and (b) autoregressive relationships of social anxiety symptoms positively reinforcing themselves. Negative self-view was the most predictable node in the network as it had the highest 'in-expected influence' centrality, and may be an important transdiagnostic outcome symptom. Conclusions: The results give insight into longitudinal interactions between symptoms, which interact in ways that do not adhere to broader diagnostic categories. Our results suggest that self-view can also be a transdiagnostic outcome of psychopathology rather than just a predictor, as is normally posited, and may especially have an important relationship with suicidal ideation. Overall, our study demonstrates the dynamic complexity of psychopathology, and further supports the importance of investigating symptom interactions of different psychopathological dimensions over time and across disorders.